Innate immunity may play a role in growth and relapse of chordoid meningioma. (December 2017) - Presta, Ivan; Guadagno, Elia; Di Vito, Anna; Malara, Natalia; Mignogna, Chiara; Maisano, Domenico; Donato, Annalidia; Cardillo, Gabriella; Del Basso De Caro, Maria Laura; Donato, Giuseppe
Chordoid meningioma (CM) is a rare subtype of meningioma, which represents only 0.5% of all meningiomas. It is classified as Grade II according to the World Health Organization classification because of its tendency to relapse. Pathological and clinical characteristics have been studied in order to forecast the future evolution of the lesions. However, information about infiltration of macrophagic elements and mast cells is very scarce. The authors analyzed the immunohistochemical patterns of three cases and a relapse of CM, in order to verify whether infiltrating macrophages are in a polarized state and what would be the proportion between such elements and mastocytes. Results suggest that macrophages in CMs are mainly in a non-polarized or M2 state and their abundance might be associated with a major potential of relapse; additionally, there is an inverse correlation between the number of mast cells and macrophages. Further studies are requested in order to confirm these intriguing data.